Pathway-specific light adaptation in human electroretinograms - Brasil, Alódia; Tsai, Tina I.; da Silva Souza, Givago; Herculano, Anderson Manoel; Ventura, Dora Fix; de Lima Silveira, Luiz Carlos; Kremers, Jan (Journal of Vision, 2019)
The cellular origins of slow ERG changes during light adaptation following a dark-adapted state are still unclear. To study light adaptation, six healthy, normal trichromats were dark-adapted for 30 min prior to full-field ERG recordings to sinusoidal stimuli that isolate responses of the L- or M-cones or that stimulate luminance and chromatic mechanisms at 12 or 36 Hz. Recordings were performed for 16 min with 2-min intervals after onset of a constant background. Generally, the responses were sine-wave-like, and the first harmonic (fundamental) component dominated the Fourier spectrum except for the 12-Hz luminance stimulus in which two components, a sine-wave-like component and a transient component, determined the response profiles, leading to large second harmonic components. The amplitude of the first harmonic component (F) increased as a function of the light-adaptation time except for the 12-Hz luminance stimulus at which the F component decreased as a function of the light-adaptation period. The phase of the first harmonic component changed only slightly (less than 30°) during the light-adaptation period for all stimuli conditions. The L/M ratio in luminance reflecting ERGs decreased with increasing adaptation time. Our present data suggest that the light-adaptation process mainly reflects changes in the luminance pathway. The responses to 12-Hz luminance stimuli are determined by two different luminance driven pathways with different adaptation characteristics.
CRIS-Team Scopus Importer:2019-05-02